A Time-Sensitive Framework for Including Geographic Information Systems (GIS) in Professional Development Activities for Classroom Teachers. Issue 4 (4th July 2017) - Millsaps, Lisa Tabor; Harrington, John A.
ABSTRACT: This work shares a time-sensitive framework for teaching GIS to educators of all levels and disciplines. Existing relationships with teachers enabled the addition of GIS content in professional development activities. The amount of time devoted to GIS-related content varied depending on time made available for interaction with the audience. Content audiences included geography, history, social studies, science, agriculture, religion, and math teachers. The framework was developed, tested, and refined over a period of six years, during thirty-six trainings, and with 580 educators. Use of this framework emphasizes that not one size fits all in GIS education and that GIS can work for any teacher, their content, their classroom, and their time availability.